The effects of multiple zincation process on Aluminum Bond Pad surface for Electroless Nickel Immersion Gold deposition - Mohd Khairuddin, Md Arshad (American Society of Mechanical Engineers (ASME), 2008)
Fulltext article is acessible via ASME Online (http://www.asme.org) or connect to A-Z Listing at http://mylib.unimap.edu.my/